Seroprevalence of Hepatitis A Twelve Years After the Implementation of Toddlers' Vaccination: A Population-Based Study in Israel. Issue 10 (October 2017) - Bassal, Ravit; Weil, Merav; Cohen, Daniel; Sofer, Danit; Mendelson, Ella; Shohat, Tamy
Abstract : Background: In 1999, Israel became the first country to introduce an inactivated hepatitis A vaccine into its national childhood vaccination program. The objective of the present study was to evaluate the seroprevalence of hepatitis A virus antibodies in the Israeli population before and after the introduction of the program. Methods: A cross-sectional serosurvey using the National Serum Bank was conducted on 1883 and 2027 serum samples collected before and after introduction of the vaccine, respectively. Serologic tests for the presence of hepatitis A IgG antibodies were performed using an automated enzyme-linked fluorescent assay. Results: The age-adjusted seroprevalence rates of hepatitis A virus antibodies before implementation of hepatitis A vaccination program were 47.1% [95% confidence interval (CI): 44.7%–49.5%] among Jews and 82.8% (95% CI: 79.6%–85.9%) among Arabs, increasing 12 years after to 67.4% (95% CI: 64.7%–70.0%) and 88.2% (95% CI: 86.1%–90.2%), respectively. Conclusions: The seropositivity rate among Jews and Arabs increased significantly among the cohorts included in the program. However, among Jews, a significant increase in seropositivity was also detected among age groups not included in the vaccination program. The decrease in the incidence of hepatitis A in Israel is a consequence of high vaccine uptake, persistent seropositivity rates after vaccination and the considerable number of people vaccinated beyond the program.